Erythrocyte Salt Sedimentation Assay Does Not Predict Response to Renal Denervation - Vonend, Oliver; Martin, Ole; Rump, Lars C.; Kroepil, Patrick; Stegbauer, Johannes (Frontiers in Medicine, 2018)
Abstract Renal denervation (RDN) has recently been shown to be effective in patients without antihypertensive medication. However, about 30 per cent of patients do not respond to RDN, and therefore, there exists a need to find predictors of response. Individuals are either salt sensitive or non-salt sensitive in terms of their blood pressure regulation. The sympathetic nervous system can influence water and salt handling. Renal Denervation reduces sympathetic drive and has an impact on salt excretion. The present study was conducted to test the influence of salt sensitivity in terms of the blood pressure reducing effect after renal denervation procedure. Salt sensitivity was estimated using the in vitro Erythrocyte Salt Sedimentation Assay (ESS). In 88 patients with resistant hypertension RDN was performed. Office blood pressure (BP) and lab testing were performed at baseline and at month 1, 3, 6, 12, 18 and 24 after renal denervation. A responder rate of 64.7% has been observed. Salt sensitivity measurements (ESS-Test) were completed in a subgroup of 37 patients with resistant hypertension. In this group, 15 were salt sensitive and 17 were salt resistant according to the in vitro assay, respectively. The responder rate was 60% in salt sensitive patients and 59.1% in non-salt sensitive patients, respectively. Electrolytes as well as aldosterone and renin levels did not differ between the two groups at baseline and in the follow-up measurements. The present study showed that salt sensitivity, estimated using the ESS in vitro test, did not affect the outcome of renal denervation and therefore does not help to identify patients suitable for renal denervation.